The Role of Digital X-Ray in Curative Effect and Nursing Evaluation of Cervical Spondylotic Radiculopathy. (17th August 2021) - Chen, Xue; Xue, Pan; Shi, Yuanyuan; Chen, Si
Abstract : The present study attempted to analyze the features of atlanto-occipital radiograph in patients with cervical spondylotic radiculopathy or vertebral artery type. In order to reduce the interference of human factors and the measurement error as much as possible, this experiment adopts the blind design and analyzes the digital format X-ray films by using the computer software ImageJ. Because the tangent line between the outer plates of the anterior and posterior margin of the foramen magnum was not accurately located on the X-ray film, the angle formed by the line between the saddle dorsal slope and the center point of the anterior and posterior nodule with a clear display was selected as the measurement method of the angle between the atlanto-occipital joints. The results showed that the lateral cervical curvature of the VCS group was 0.43 ± 0.51, and the lateral cervical curvature of the CSR group was 0.46 ± 0.49, both of which were significantly lower than the normal value (1.2 ± 0.5 cm). Patients in both groups had the characteristic of cervical curvature straightening. The changes of cervical curvature in overflexion and overextension positions can indirectly reflect the state of cervical motion. The anterior flexion neck curve of the VCS group was less than that of the CSR group (P < 0.05 ). Compared with the CSR group, VCS showed limited cervical anterior flexion movement. In this study, X-ray films of both CSR and VCS showed occipitocervical flexion and extension disorders, cervical curvature straightening, and lower cervical instability. In VCS, occipitocervical flexion and extension disorders were mainly manifested in atlantoaxial flexion disorders, while in CSR, atlanto-occipitocervical flexion and extension disorders were mainly manifested in atlantoaxial flexion disorders.